Nanoscale order in the frustrated mixed conductor La5.6WO12−δ. Issue 3 (1st June 2016) - Scherb, Tobias; Kimber, Simon A. J.; Stephan, Christiane; Henry, Paul F.; Schumacher, Gerhard; Escolástico, Sonia; Serra, José M.; Seeger, Janka; Just, Justus; Hill, Adrian H.; Banhart, John
Abstract : A combination of neutron and X‐ray diffraction together with pair distribution function and EXAFS analysis is shown to solve the crystal structure for the highly disordered proton and electron conductor La5.6 WO12−δ on average and local length scales. Abstract : This article reports a comprehensive investigation of the average and local structure of La5.6 WO12−δ, which has excellent mixed proton, electron and oxide ion conduction suitable for device applications. Synchrotron X‐ray and neutron powder diffraction show that a cubic fluorite supercell describes the average structure, with highly disordered lanthanum and oxide positions. On average, the tungsten sites are sixfold coordinated and a trace [3.7 (1.3)%] of anti‐site disorder is detected. In addition to sharp Bragg reflections, strong diffuse neutron scattering is observed, which hints at short‐range order. Plausible local configurations are considered and it is shown that the defect chemistry implies a simple `chemical exchange' interaction that favours ordered WO6 octahedra. The local model is confirmed by synchrotron X‐ray pair distribution function analysis and EXAFS experiments performed at the La K and W L 3 edges. It is shown that ordered domains of ∼3.5 nm are found, implying that mixed conduction in La5.6 WO12−δ is associated with a defective glassy‐like anion sublattice. The origins of this ground state are proposed to lie in the non‐bipartite nature of the face‐centred cubic lattice and the pairwise interactions which link the orientation of neighbouring octahedral WO6 sites. This `function through frustration' could provide a means of designing new mixed conductors.